RURAL COMMUNITY PERCEPTIONS OF CLIMATE CHANGE IMPACTS ON FARMERS' WELFARE - Ningrum, Diyah Ulan (Universitas Lambung Mangkurat, 2024)
Climate change significantly challenges the agricultural sector, affecting crop yields and farmers' livelihoods. A decline in harvest yields leads to reduced income for farmers, impacting their overall well-being. This study aims to analyze rural farmers' perceptions of the impact of climate change on their welfare. The research employs a qualitative approach, using in-depth interviews as the primary data collection method. The findings reveal that climate change poses major challenges to agriculture, including changes in plant growth and development patterns. These challenges result in decreased productivity, lower selling prices, and reduced wages for farmers, ultimately leading to decreased welfare. These findings provide critical insights into the effects of climate change on farmers' lives. They can serve as a foundation for developing policies that support farmers' well-being amid global climate change.